Determination of the Interaction and Pharmacological Modulation of MCHR1 Signaling by the C-Terminus of MRAP2 Protein - Wang, Meng; Zhai, Yue; Lei, Xiaowei; Xu, Jing; Jiang, Bopei; Kuang, Zhe; Zhang, Cong; Liu, Shangyun; Bian, Shan; Yang, Xiao-Mei; Zan, Tao; Jin, Li-Na; et al. (Frontiers in Endocrinology, 2022)
Melanin concentrating hormone (MCH), an orexigenic neuropeptide, is primarily secreted by the hypothalamus and acts at its receptor, the melanin-concentrating hormone receptor 1 (MCHR1) to regulate appetite and energy homeostasis. The Melanocortin Receptor Accessory Protein 2 (MRAP2), a small single transmembrane protein broadly expressed in multiple tissues, has been defined as a vital endocrine modulator of five melanocortin receptors (MC1R-MC5R) and several other GPCRs in the regulation of central neuronal activities and peripheral energy balance. Here, we demonstrated the interaction between MRAP2 and MCHR1 by immunoprecipitation and bimolecular fluorescent assay and found that MRAP2 could inhibit MCHR1 signaling in vitro. A series of functional truncations of different regions further identified the C-terminal domains of MRAP2 protein were required for the pharmacological modulation of intracellular Ca2+ coupled cascades and membrane transport. These findings elucidated the broad regulatory profile of MRAP2 protein in the central nervous system and may provide implications for the modulation of central MCHR1 function in vivo.